Combination of Albumin-Globulin Score and Sarcopenia to Predict Prognosis in Patients With Renal Cell Carcinoma Undergoing Laparoscopic Nephrectomy - Mao, Weipu; Zhang, Nieke; Wang, Keyi; Hu, Qiang; Sun, Si; Xu, Zhipeng; Yu, Junjie; Wang, Can; Chen, Saisai; Xu, Bin; Wu, Jianping; Zhang, Hua; et al. (Frontiers in Nutrition, 2021)
We conducted a multicenter clinical study to construct a novel index based on a combination of albumin-globulin score and sarcopenia (CAS) that can comprehensively reflect patients' nutritional and inflammatory status and assess the prognostic value of CAS in renal cell carcinoma (RCC) patients. Between 2014 and 2019, 443 patients from three centers who underwent nephrectomy were collected (343 in the training set and 100 in the test set). Kaplan-Meier curves were employed to analyze the impact of albumin-globulin ratio (AGR), albumin-globulin score (AGS), sarcopenia, and CAS on overall survival (OS) and cancer-specific survival (CSS) in RCC patients. Receiver operating characteristic (ROC) curves were used to assess the predictive ability of AGR, AGS, sarcopenia, and CAS on prognosis. High AGR, low AGS, and nonsarcopenia were associated with higher OS and CSS. According to CAS, the training set included 60 (17.5%) patients in grade 1, 176 (51.3%) patients in grade 2, and 107 (31.2%) patients in grade 3. Lower CAS was linked to longer OS and CSS. Multivariate Cox regression analysis revealed that CAS was an independent risk factor for OS (grade 1 vs. grade 3: aHR=0.08; 95% CI: 0.01-0.58, p=0.012; grade 2 vs. grade 3: aHR=0.47; 95% CI: 0.25-0.88, p=0.018) and CSS (grade 1 vs. grade 3: aHR=0.12; 95% CI: 0.02-0.94, p=0.043; grade 2 vs. grade 3: aHR=0.31; 95% CI: 0.13-0.71, p=0.006) in RCC patients undergoing nephrectomy. Additionally, CAS had higher accuracy in predicting OS (AUC=0.687) and CSS (AUC=0.710) than AGR, AGS, and sarcopenia. In addition, similar results were obtained in the test set. The novel index CAS developed in this study, which reflects patients' nutritional and inflammatory status, can better predict the prognosis of RCC patients.